2020
DOI: 10.1111/jcmm.15755
|View full text |Cite
|
Sign up to set email alerts
|

SATB2 is a novel biomarker and therapeutic target for cancer

Abstract: Gene expression is tightly controlled by epigenetic regulators and transcription factors. One such factor is SATB2 (special AT-rich binding protein-2) which influences gene expression by regulating chromatin architecture and by acting as a transcriptional co-factor. 1-5 This gene is conserved in humans and mouse. In humans, there are three transcripts which encodes for SATB2 protein. Genetic engineering techniques have demonstrated that SATB2 knockout mice are defective in bone development and osteoblast diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 63 publications
1
36
0
1
Order By: Relevance
“…TargetScan ( ) was used to search for candidate targets with potential miR-875 binding sites. It was observed that there was a common binding site between miR-875 and the 3′-untranslated region of SATB2, a tumor suppressor ( 23 ), which was further verified using a luciferase reporter assay ( Fig. 5A ).…”
Section: Resultsmentioning
confidence: 67%
“…TargetScan ( ) was used to search for candidate targets with potential miR-875 binding sites. It was observed that there was a common binding site between miR-875 and the 3′-untranslated region of SATB2, a tumor suppressor ( 23 ), which was further verified using a luciferase reporter assay ( Fig. 5A ).…”
Section: Resultsmentioning
confidence: 67%
“…HPNE cells were grown in a cell culture medium in the presence or absence of ethanol (10 mM and 100 mM) for 6 months. Studies have shown the role of SATB2 in chromatin remodelling and regulation of genes, which participate in cell growth, survival, differentiation, self‐renewal, and pluripotency 28–31,39 . We therefore examined the mechanism of ethanol‐induced EMT characteristics in HPNE cells by comparing the expression of SATB2 in HPNE control cells and ethanol‐transformed HPNE cells (HPNE/Ethanol).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown the role of SATB2 in chromatin remodelling and regulation of genes, which participate in cell growth, survival, differentiation, self‐renewal, and pluripotency. 28 , 29 , 30 , 31 , 39 We therefore examined the mechanism of ethanol‐induced EMT characteristics in HPNE cells by comparing the expression of SATB2 in HPNE control cells and ethanol‐transformed HPNE cells (HPNE/Ethanol). As shown in Figures 1A 6‐month exposure of HPNE cells to ethanol had induced the expression of SATB2 gene.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 1, we present the facial features of several of the participants in this study. Given SATB2 differential expression in various cancers and its significant role in cancer initiation, progression, and metastasis, it has been postulated as an oncogene (Roy et al, 2020). In this study, no cancers or tumors were reported.…”
Section: Discussionmentioning
confidence: 99%